1985
DOI: 10.1001/jama.1985.03350320075020
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Danazol Treatment in Patients With Hemophilia A (Classic Hemophilia)

Abstract: Danazol, an attenuated androgen, was given intermittently in three patients with hemophilia A. The rise in factor VIII activity with danazol treatment was associated with a fivefold decrease in hemorrhagic episodes and plasma concentrate product utilization when compared with similar periods without the drug. Four other patients with moderate hemophilia A who received danazol for 14 days had an increase of 400% to 850% in their factor VIII levels. Of four patients without detectable levels of factor VIII who w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

1985
1985
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 6 publications
2
7
1
Order By: Relevance
“…This effect, however, appears more general and not specific for the factor IX Leyden gene because similar effects were also seen for other proteins, such as factor VIII (25)(26)(27). Our results obtained from the in vitro assay system agree well with this observation.…”
Section: Methodssupporting
confidence: 87%
“…This effect, however, appears more general and not specific for the factor IX Leyden gene because similar effects were also seen for other proteins, such as factor VIII (25)(26)(27). Our results obtained from the in vitro assay system agree well with this observation.…”
Section: Methodssupporting
confidence: 87%
“…These results were initially confirmed by the same authors in 11 patients with hemophilia A [16]; how ever, others observed either minimal in creases in factor levels, no decrease in bleed ing tendency or an excess of adverse effects [5,17], In the only randomized placebo-con trolled trial of danazol in hemophilia A. Metha et al [18] observed that only some pa tients with hemophilia A obtained a signifi cant increase in factor VIII levels, but that responders appeared to benefit clinically from this increased factor level. No adverse effects were seen during 3 months of treatment with 300 mg/day of danazol in this study [ 18], In 1980, Fiessinger and Aiach [ 19] gave an 8-month course of stanozolol to a patient with hereditary antithrombin III deficiency.…”
Section: Discussionsupporting
confidence: 59%
“…It is possible that the response seen in our case was because of the longer duration of therapy and/or a higher baseline FX level in contrast to that reported by Sumer et al It is also possible that the response to danazol may be characteristic of particular genetic variants of factor-de®cient patients [11]. Gralnick et al have postulated that the varying response to danazol re¯ects the heterogeneity of the basic pathogenesis of haemophilia [7]. Some patients may have functional genes that can be activated by androgens such as danazol whereas others may have abnormal genes or abnormal regulatory mechanisms that cannot be activated.…”
Section: Discussioncontrasting
confidence: 52%